Tyrosine Kinase Inhibitor Resistance in Patients with Chronic Myeloid Leukemia: A 10-Year Study of BCR-ABL Gene Mutation Profile in Russia (2006–2016) - VV Tikhonova; MA Isakov; VA Misyurin; YuP Finashutina; LA Kesaeva; NA Lyzhko; IN Soldatova; NN Kasatkina; EN Misyurina; AV Misyurin (Клиническая онкогематология)
Background. Kinase domain mutations of BCR-ABL gene is the most common cause of tyrosine kinase inhibitor resistance.